General Approaches to the Market Structure Control in BRICS Countries - FROLOVA, Evgenia Evgenevna; BELIKOVA, Ksenia Mikhailovna; BADAEVA, Natalia Vladimirovna; AKHMADOVA, Maryam Abdurakhmanovna; DUDIN, Mihail Nikolaevich (Journal of Advanced Research in Law and Economics, 2018)
The articles represents a research of general approaches of BRICS countries legislation and legal order to counteraction against such an anticompetitive market strategy and a means of both global and regional governance as abuse of control and dominant market power in legal orders of China, India, Russia and South Africa. The author pays particular attention to current legislation of BRICS countries in the field of competition protection with regard to provisions related to market structure control and restrictions of anticompetitive mergers and acquisitions (further on - M&As) and ‘concentrationʼ of enterprises' market power control fixed by Asian (China and India), Euro-Asian (Russia) and African (South Africa) legal orders. The analysis of substantial contents of laws on competition and monopolies of the abovementioned BRICS countries and relevant case law shows the existence of a number of conventional generally acknowledged (unified) provisions and norms. At the same time there are specific features making them different. These generally acknowledged provisions and peculiarities will be in focus in the article.